Analisis Kebijakan Prinsip Governance dan Aktor Melalui Analytical Hierarchy Process (AHP) dalam Perencanaan Kota - Bambang Utoyo Sutiyoso (Spirit Publik: Jurnal Administrasi Publik, 2017)
Urban spatial planning as a part of spatial planning activities actually is a form of public policy formulation related with urban space management. Actions done by the policy actor in the formulation process of public policy will be extremely determined by the perspectives used. Governance as the main perspective in public administration and management demands the application of principles which attributed to it in order to achieve good governance. Based on that, the problem of the research is: how is the priority of the governance principles related to the actor/agent involved in urban planning? The purposes of the research are to know, to describe, and to analyze the priority of governance principles related to the actor/agent involved in urban planning. The type of the research, basically, is a descriptive research using the quantitative model analysis, that is Analythical Hierarchy Process. Data sources are taken from the research respondents which are consisting of municipal government elements; civil society and private (business) sector.The result shows that the priorities of governance principles application in urban planning based on the involved actor/agent are:  first: participation (3.141); second: responsive (3.021); third : transparancy (3.009); and fourth : accountability (2.867), with the actors value: civil society (1.168); municipal government (1.096); and business (private) sector by the value of (0.736) respectively. Civil society participation is done to the whole phases of urban planning in the form of providing data and information, opinion and aspiration, as well as objection and rebuttal toward the concept of city territorial development.  Meanwhile, practically, the research recommends the need of regulation toward the civil society participation in urban planning in local nature to find the best practice; the application of governance principles should become the mindset of public officer and the planner in spatial planning.